Improved malted barley brings new income potential to farmers - International Livestock Research Institute (International Livestock Research Institute, 2021)
This film profiles the works of Africa RISING in Ethiopia. It explains how the new high yielding malt barley varieties introduced through the project have the potential to revolutionize the barley sector and help to support growing domestic demand and greatly raise farmer incomes. More information: https://africa-rising.net/